Cost and return analysis of investment on oyster mushroom farming in Nakhon Pathom : Case Study Learning resources - Thaneerananon, Arisara; Vilala, Premarat (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The research aim to 1. Study cost and return on investment of oyster mushroom farming in Nakhon Pathom 2. To analyze cost and return on investment of oyster mushroom farming in Nakhon Pathom : Case Study Learning resources. The samples of this study were the entrepreneur of oyster mushroom in Nakhon Pathom province which comprises of Amphoe Muang Nakhon Pathom, Amphoe Kamphaeng Saen, Amphoe Don Toom, Amphoe Nakhon Chaisi, Amphoe Bang Lane, Amphoe Putthamonthon, Amphoe Samphran. The tools used in this research were the interview of oyster mushroom operators in Nakhon Pathom, the analysis of cost and return of investment on oyster mushroom farming in Nakhon Pathom and document analysis by using content analysis. The results showed that 1. Cost and return of investment on oyster mushroom farming in Nakhon Pathom can be classified as mushroom farming by buying chunk of mushroom to plant and launch mushroom, and mushroom farming by producing chunk of mushroom to plant and launch mushroom. 2. Cost analysis and return by using breakeven analysis which is approximately 584 units of mushroom chunks so could be harvested approximately 234 kilograms of mushroom, at the present wholesale price of mushroom was 50 baht per kilogram. In the cost of 3x4 meters housing which could be placed 1,500 chunks of mushroom with the average housing cost is approximately 7,000 baht. Moreover, one chuck of mushroom could be harvested up to 400 grams in average for 3 months to 3 months and 15 days of mushroom harvesting. The payback period analysis can be found that the total cost could be paid back in the first quarter of chunk mushroom investment, which approximately 2 months and 5 days, and in the next quarter, the net investment especially for mushroom chunks and watering has the average payback period about 1 month and 15 days, at the average price of mushroom chunk was 10 baht. Article history : Received 10 October 2018 Revised 24 August 2019 Accepted 29 April 2019 SIMILARITY INDEX = 0.98